PENEGAKAN HUKUM TINDAK PIDANA PELAYARAN PADA KAPAL YANG MENGANGKUT BARANG KHUSUS DAN BARANG BERBAHAYA DI KSOP KELAS II TARAKAN - RAHMAN, ABD.; SYAFRUDDIN, SYAFRUDDIN; SALINDING, MARTHEN B. (JURNAL AKTA YUDISIA, 2025)
Law enforcement in the shipping sector is essential to ensure maritime safety, as regulated in Law No. 17 of 2008 on Shipping. In KSOP Class II Tarakan, many traditional cargo vessels, particularly ships transporting special and hazardous goods, still fail to meet requirements, which can potentially constitute shipping crime under Article 246(1) with penalties of up to 3 years imprisonment or fines of IDR 400 million. However, law enforcement is hindered by weak inter-agency coordination, as maritime forums remain ineffective, leading to fragmented supervision and imbalanced sea patrols.